1995
DOI: 10.1111/j.1600-0668.1995.t01-2-00003.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Climatic Parameters on Formaldehyde Concentrations in Indoor Air

Abstract: The results of measurements of indoor air formaldehyde concentrations in occupational and private residences are presented for the period 1986 to 1993, based on requests of persons who complained about irritations. In many cases, climatic parameters such as the air exchange rate, temperature and relative humidity were also monitored. Calculated mean values for temperature and humidity were 22°C and 45% respectively. The average air exchange rate was 0.36 h−1, which is well below a recommended guideline value o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 14 publications
(21 reference statements)
2
30
0
1
Order By: Relevance
“…The 50 th percentile (median) of the ACR was 0.2 h -1 with a 95% confidence interval (CI) of 0.17 h -1 -0.24 h -1 ; arithmetic mean was 0.31 h -1 (95% CI 0.27 h -1 -0.36 h -1 ) and geometric mean was 0.22 h -1 (95% CI 0,20 h -1 -0,25 h -1 ), respectively (see Table 10). Thus, our studies essentially confirm the results obtained by Münzenberg (2004) and Salthammer et al (1995), who conducted ACR measurements under similar methodological conditions in Germany, and received results consistent with those from surveys in Scandinavia by Andersen et al (1997); Bornehag et al (2005) and Harving et al (1992).…”
Section: Air Change Rates In Berlin's Housing Stocksupporting
confidence: 81%
See 1 more Smart Citation
“…The 50 th percentile (median) of the ACR was 0.2 h -1 with a 95% confidence interval (CI) of 0.17 h -1 -0.24 h -1 ; arithmetic mean was 0.31 h -1 (95% CI 0.27 h -1 -0.36 h -1 ) and geometric mean was 0.22 h -1 (95% CI 0,20 h -1 -0,25 h -1 ), respectively (see Table 10). Thus, our studies essentially confirm the results obtained by Münzenberg (2004) and Salthammer et al (1995), who conducted ACR measurements under similar methodological conditions in Germany, and received results consistent with those from surveys in Scandinavia by Andersen et al (1997); Bornehag et al (2005) and Harving et al (1992).…”
Section: Air Change Rates In Berlin's Housing Stocksupporting
confidence: 81%
“…Generally insufficient fresh air supply resulted in an considerable increase of indoor air pollutants. This is the case for formaldehyde (Li et al, 2002;Salthammer et al, 1995;Wegner, 1983) and other volatile compounds (Hodgson et al, 2003) as well as for the radioactive noble gas radon (Andersen et al, 1997;Chao et al, 1997;Sentikova, 1999). Our own studies also found a correlation between the concentration of volatile organic compounds and the ventilation rate in naturally ventilated rooms, as described below.…”
Section: Ventilation and Pollutant Concentrationsmentioning
confidence: 99%
“…Dust mite allergen is associated with allergies and asthma [118]. The risks of indoor dampness and mold growth, associated with respiratory and asthma symptoms [40] are diminished by avoiding high indoor humidity values and the indoor levels of formaldehyde will be reduced because indoor formaldehyde emission rates decrease with decreased indoor humidity [119]. On the other hand, during the heating season when the moisture content of indoor air is often higher than the moisture content of outdoor air, envelope air tightening, without compensating measures, will increase indoor air humidity.…”
Section: Ozonementioning
confidence: 99%
“…New homes typically have the highest concentrations of formaldehyde and other VOCs that are emitted from new building materials or new furnishings brought into the home (Dingle and Franklin 2002;Park and Ikeda 2006). Homes with lower outdoor air exchange rates, a condition that occurs when building envelopes are tightened to reduce uncontrolled infiltration, also typically have higher concentrations of VOCs from indoor sources (Salthammer et al 1995).…”
Section: Introductionmentioning
confidence: 99%